IMPLEMENTATION OF REGENERATIVE TOURISM IN THE DEVELOPMENT OF TOURISM DESTINATIONS IN INDONESIA - Radyahadi, Fadhlan; Nurfara, Najma Afifa (Politeknik Pariwisata NHI Bandung, 2024)
In the last few decades, a travel-based activity with a purpose of traveling has become one of the most important developments in the economic sector around the world. The development of tourism in a region has not only giving a positive impact but also a negative impact on the destination. Tourism has a major impact on the environment (such as; biodiversity loss, landscape impact, waste and water scarcity) and social impact (such as; over tourism, gentrification and social uprising). Regenerative tourism has the idea that tourism activities should leave something better at the destination than the previous circumstances. Unlike the concept of sustainable tourism that requires leaving the destination as it should without changing or causing more additional damage. The COVID-19 pandemic shows that the tourism sector is highly vulnerable, but on the other hand it is also an opportunity to rethink how to develop tourism. Regenerative tourism is presented as a new idea or concept in tourism as a way of thinking about how to rebuild tourism more better. Thus, the implementation of regenerative tourism policies can make the world better as it used to be by restoring landscapes and teaching tourists skills that can be applied in their country or region of origin